Comparison of patients history taking and physical examination in traditional Iranian medicine and common medicine: A library review - M Mortaghi Ghasemi (Babol University of Medical Sciences, 2019)
Considering the history and semiotics of diseases, especially significant in the viewpoint of ancient Iranian physicians in traditional medicine as well as in traditional medicine, and it is one of the first doctrines and first teachings of scholars and professors to medical students. Comparing his point of view shows a common point about how to deal with the patient and how to describe patients are among the first and most basic training and important step in the correct diagnosis, without is commonly used in paraclinical methods. The purpose of this study is to determine the viewpoints of traditional medicine in Iran and its current state in current medicine. In the present article, after reviewing the main sources of traditional medicine and common medicine, the results of the comparative study that as traditional medicine is important attention to the obtaining history and physical examination of patients. Traditional medicine and contemporary medicine, has also devoted to its role incorrect diagnosis and proper treatment and devised new methods and approaches to make, it works better and more efficiently. The criteria for the entry of resources into the research of books in the field of traditional medicine such as law, Kamel al-Sinaah, Khofi alayi, al-Mansouri ... and in the current medical practice of physical examinations of Bits and ... were also related articles However, with the arrival of clinical and paraclinical facilities, attention to histories and physical examinations has lost its importance in comparison with the past. In this article, we have tried to compare the view of the two medicine with an emphasis on physical examinations and history of the patient.